h-Adic Polynomials and Partial Fraction Decomposition of Proper Rational Functions over R or C - Kwang Hyun Kim; Xin Zhang (International Journal of Mathematics and Mathematical Sciences)
The partial fraction decomposition technique is very useful in many areas including mathematics and engineering. In this paper we present a new and simple method on the partial fraction decomposition of proper rational functions which have completely factored denominators over R or C. The method is based on a recursive computation of the h-adic polynomial in commutative algebra which is a generalization of the Taylor polynomial. Since its computation requires only simple algebraic operations, it does not require a computer algebra system to be programmed.